Discrimination of a nerve fiber that is the origin of a cauda equina tumor using acetylcholinesterase staining. Issue 5 (11th May 2017) - Kamei, Naosuke; Tanaka, Nobuhiro; Arihiro, Koji; Nakanishi, Kazuyoshi; Kotaka, Shinji; Adachi, Nobuo; Ochi, Mitsuo
Abstract : Spinal nerve sheath tumors are well known to typically originate from dorsal sensory nerve roots. However, it is difficult to anatomically identify the origin in the case of cauda equina tumors. In this study, we aimed to ascertain whether a cauda equina nerve root removed with a nerve sheath tumor was a motor nerve using acetylcholinesterase (AchE) staining. Nerve rootlet sections removed with tumors were stained for AchE using the AchE Rapid Staining Kit. Additionally, we performed intraoperative motor‐evoked potential (MEP) monitoring following either transcranial electrical stimulation (TES) or electrical stimulation of nerve rootlets. The muscular strength of the lower extremities was assessed bilaterally before and after surgery using manual muscle testing. An AchE‐positive motor nerve rootlet that was the origin of a cauda equina tumor was observed in one of the 12 patients. In this patient, a MEP in the right quadriceps evoked by electrical stimulation of this rootlet was detected. TES‐MEP showed a 30% decrease in the amplitude in the right quadriceps evoked after tumor resection with this nerve rootlet. However, the motor strength in both lower extremities did not change after surgery. AchE staining and intraoperative MEP monitoring could detect the motor nerve rootlet that was the origin of a cauda equina tumor. Nerve sheath tumors originating from the motor nerve might be rare even in cauda equina.